Codex-Convolutes BnF Supplément Grec 607: Paleography, Codicology and Time of Making - Marina Kurysheva (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
The Greek manuscript-convolute BnF Suppl. gr. 607, consisting of five parts united under one binding, has not yet been the subject of a comprehensive codicological analysis, nor has a paleographic study of all its individual parts been carried out. In the paper, with the help of paleographic analysis, all these parts were dated: the paper sheet with the owner’s inscription and four riddles – the end of the 16th century; fragments of the “History” by Nicetas Choniates from the first half to the middle of the 13th century; fragments of homilies by John Chrysostom from the end of the 11th to the beginning of the 12th century; an incomplete collection of Ancient and Byzantine passages from historians and excerpts from military treatises from the end of the 9th to the beginning of the 10th century; fragments of orator Lysias’ speeches from the second half of the 15th to the 16th centuries. On the basis of the analysis of codicology and the data available to us about the activity of its first owner, Minoides Minas, it is concluded that this convolute was made by him himself from the remains of the codices, which were previously separate. And it is concluded that there is no evidence that any parts were combined earlier. The 1510s binding was either acquired separately and used as a folder for valuable fragments of various manuscripts or belonged to one of the five parts, possibly a codex of Lysias' speeches.